2006
DOI: 10.1159/000095650
|View full text |Cite
|
Sign up to set email alerts
|

Field Trial on Caries Prevention with Xylitol Candies among Disabled School Students

Abstract: Background: In a 1999 survey high caries levels were found among physically disabled school students in Kuwait. Objectives: A field study was planned to test the efficacy of xylitol candies in preventing caries among individuals in two special schools in Kuwait. Methods: Altogether 176 students were examined in 2002 and 145 (105 in xylitol group and 40 in the control group) after 18 months’ intervention. The WHO criteria were used in recording caries according to surfaces (third molars were excluded) by 2 cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
12

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 36 publications
1
63
1
12
Order By: Relevance
“…It is already known that the use of fluoride is effective in minimizing dental decay (11). What is more, the simultaneous application of xylitol and fluoride produces a synergistic effect, but the precise mechanism of synergism is unknown (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that the use of fluoride is effective in minimizing dental decay (11). What is more, the simultaneous application of xylitol and fluoride produces a synergistic effect, but the precise mechanism of synergism is unknown (20).…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol is a natural five-carbon-sugar alcohol that can be safely applied as a preventive measure for diseases such as pneumonia, acute otitis media (AOM), dental caries, and meningitis (11,16,21,38,41,45,47). The causative pathogens of pneumonia in children are Gram-positive Streptococcus pneumoniae and Gram-negative Klebsiella pneumoniae with polysaccharide capsules.…”
mentioning
confidence: 99%
“…A number of observational studies and clinical trials have shown the caries-protective effect of xylitol, and to a lesser extent sorbitol (Honkala et al 2006, Burt 2006, Anderson 2003, Hayes 2001. For the first time, comprehensive Finnish "Turku Sugar Study" (Scheinin et al 1976) revealed an 85% decline in dental caries by total dietary substitution of sucrose with xylitol over a 2-year period.…”
Section: Non-cariogenic Sweetenersmentioning
confidence: 99%
“…The effect of maternal use of xylitol chewing gum on caries and on mutans streptococci in children has been shown to be beneficial in caries reduction, with significantly less The use of xylitol products has also been tested on patients with high caries risk, with fixed orthodontic appliances, disabled school children and/or veterans with high root caries risk. [30][31][32] Xylitol appeared to have caries preventive effects in all but one of these studies. However, in a two-year double blind trial evaluating the effect of xylitol-and xylitol/fluoride-containing lozenges on proximal caries, no statistically significant differences were found in caries incidence between the experimental groups and a control group that did not receive lozenges.…”
Section: Clinical Trials With Xylitolmentioning
confidence: 99%